Hobos, hustlers, and backsliders: homeless in San Francisco - Gowan, Teresa (University of Minnesota Press, 2010)
Urban ethnography beyond the culture wars -- Managing homelessness in the United States -- The street : watch out, San Francisco! Ain't gonna get no peace -- Moorings : some other kind of life -- Word on the street : no one loves a loser -- The new hobos -- Rabble management : like I need more drugs in my life? -- The homeless archipelago : a little room for myself -- The old runaround : class cleansing in San Francisco -- The road to Nowheresville